Teprotumumab in Clinical Practice: Recommendations and Considerations From the OPTIC Trial Investigators. Issue 4 (1st December 2021) - Douglas, Raymond S.; Wang, Yao; Dailey, Roger A.; Harris, Gerald J.; Wester, Sara T.; Schiffman, Jade S.; Tang, Rosa A.; Fowler, Brian; Fleming, James; Smith, Terry J.
Abstract : Background: Thyroid eye disease (TED) is a vision-threatening and debilitating condition that until very recently had no Food and Drug Administration (FDA)-approved medical therapies. Teprotumumab has recently been approved to treat TED. We aim to provide guidance for its use, based on the input of the US investigators who participated in Phase 2 and Phase 3 clinical trials. Methods: An expert panel was convened on October 11th and November 16th of 2019. All panel members had extensive experience as investigators in the Phase 2 and/or Phase 3 clinical trials of teprotumumab. Consensus among those investigators was reached to determine patient characteristics most appropriate for teprotumumab treatment. Safety guidelines were also reviewed and agreed on. Results: The authors recommend that teprotumumab be considered first-line therapy for patients with clinically significant ophthalmopathy, including those with disease duration exceeding 9 months. The clinical activity score (CAS) may be useful for longitudinal monitoring but should not be used to determine treatment eligibility. Criteria will likely be expanded after more experience with the drug. Using teprotumumab for patients with TED with substantial signs, symptoms, or morbidity without a CAS score of >4 (e.g., progressive proptosis, diplopia, and early compressive optic neuropathy) or more, could be considered. Diabetes mellitus and inflammatory bowel disease comorbidities should not be exclusionary, but stringent monitoring in these patients is recommended. Drug dosing, administration interval, and duration should adhere to the study protocol: 8 infusions, separated by 3 weeks. Patients with more severe disease may benefit from additional doses. Corticosteroids can be used before or during teprotumumab therapy. Clinical and laboratory monitoring should be consistent with good clinical practice for patients receiving teprotumumab. Conclusions: Confirming the efficacy of teprotumumab usage outside the narrow parameters of the completed clinical trials will require rigorous scientific validation. As a step in that direction, we believe its on-label usage is appropriately applied to all patients with TED with substantial symptoms or morbidity, as judged by their physician.